Posttranslational Modifications of Proopiomelanocortin in Vertebrates and Their Biological Significance - Takahashi, Akiyoshi (Frontiers Media S.A., 2013)
Proopiomelanocortin (POMC) is the precursor of several peptide hormones generated in the pituitary gland. After biosynthesis, POMC undergoes several posttranslational modifications, including proteolytic cleavage, acetylation, amidation, phosphorylation, glycosylation, and disulfide linkage formation, which generate mature POMC-derived peptides. Therefore, POMC is a useful model for the investigation of posttranslational modifications. These processes have been extensively investigated in mammals, primarily in rodents. In addition, over the last decade, much information has been obtained about the posttranslational processing of POMC in non-mammalian animals such as fish, amphibians, reptiles, and birds through sequencing and peptide identification by mass spectrometry. One POMC modification, acetylation, is known to modulate the biological activities of POMC-derived α-melanocyte-stimulating hormone (α-MSH) having an acetyl group at N-terminal through potentiation or inhibition. This bidirectional regulation depends on its intrinsic roles in the tissue or cell; for example, α-MSH, as well as desacetyl (Des-Ac)-α-MSH, stimulates pigment dispersion in the xanthophores of a flounder. In contrast, α-MSH does not stimulate pigment dispersion in the melanophores of the same species, whereas Des-Ac-α-MSH does. Regulation of pigment-dispersing activities may be associated with the subtle balance in the expression of receptor genes. In this review, we consider the posttranslational modifications of POMC in vertebrates from an evolutionary aspect, with a focus on the relationship between acetylation and the biological activities of α-MSH as an important consequence of posttranslational modification.